Serratia marcescens endogenous endophthalmitis in an immunocompetent host. (20th January 2016) - Memon, Muhammad; Raman, Vasant
Abstract : A systemically well 66-year-old white Caucasian man presented to the urgent care department with a short history of progressive pain and blurring of vision in his left eye. He denied a history of trauma, intraocular surgery or use of illicit drugs. He was diagnosed with endogenous endophthalmitis. Vitreous biopsy grew Serratia marcescens, a Gram negative bacteria. In spite of extensive investigation, there was no obvious source of infection. He had an indwelling urine catheter for prostate hypertrophy, but urine culture was negative. There was no evidence of immunocompromise. He was treated with systemic as well as intravitreal antibiotics. In spite of appropriate treatment, the patient lost vision. S. marcescens endophthalmitis, seen even in immunocompetent people, carries a poor visual prognosis.